Direct Measurement of Tissue Oxygenation as a Method of Diagnosis of Acute Compartment Syndrome. Issue 11 (November 2016) - Weick, Jack W.; Kang, Heejae; Lee, Lawrence; Kuether, Justin; Liu, Xuhui; Hansen, Erik N.; Kandemir, Utku; Rollins, Mark D.; Mok, James M.
Abstract : Objective: The aim of this study was to investigate the utility of direct measurement of tissue oxygenation during compartment syndrome (CS) and tourniquet-induced ischemia in a large animal model. We hypothesize that as compartment pressure (CP) rises, circulation within the compartment will decrease resulting in a decreased level of oxygen in the muscle. Methods: This study used a dog model of both CS- and tourniquet-based ischemia. In 15 animals, CS was induced in 1 hind limb with varying degrees of severity using an infusion model. Tourniquet ischemia was induced in the contralateral hind limb for varying durations. The partial pressure of oxygen (PmO2 ) was continuously monitored using a polarographic oxygen probe in the muscle of both hind limbs. CP was monitored in the CS limb. PmO2 and CP were analyzed after fasciotomy, performed after approximately 7 hours of warm ischemia, or release of tourniquet. Results: With the application of tourniquet ischemia, PmO2 fell from 38.40 to 1.30 mm Hg ( P < 0.001) and subsequently rose after release of the tourniquet to 39.81 mm Hg ( P < 0.001). Elevated CP induced by infusion was relieved by fasciotomy (52.04–11.37 mm Hg postfasciotomy, P < 0.001). PmO2 readings in the infusion model were significantly higher in pre-CS than during CS (31.77 mm Hg vs. 3.88 mm Hg, P < 0.001) and rebounded after fasciotomy (50.24 mm Hg, P < 0.001), consistent with hyperemic response. Conclusions: Increased CP caused an observable decrease in PmO2 that was reversed by fasciotomy. PmO2 can be directly measured in real time with a polarographic tissue pO2 probe. This study is the first step of evaluating an alternative method for diagnosing acute CS. Abstract : Supplemental Digital Content is Available in the Text.